ASSESSMENT OF SUSTAINABLE DEVELOPMENT IN AGRICULTURE: SYSTEM OF INDICATORS AND METRICS - Ergashev, Gayrat Urolovich (THE INNOVATION ECONOMY, 2026)
This article provides a scientific analysis of a comprehensive assessment system for sustainable agricultural development, including its key indicators and metrics. The research is based on framework approaches developed by the FAO (Food and Agriculture Organization), OECD, the World Bank, and the United Nations Sustainable Development Goals (SDGs). A total of 47 core indicators across economic, environmental, social, and governance dimensions were analyzed, and their applicability at global and regional levels was evaluated. The methodology for measuring sustainability in agriculture has been systematized based on international experience, and recommendations for its adaptation to the conditions of Uzbekistan have been developed. The findings indicate that integrated multidimensional assessment systems have 2.4 times greater informational capacity compared to single economic indicators.